Summer Olympic sports and female athletes: comparison of anti-doping collections and prohibited substances detected in Australia and New Zealand vs. France - Buisson, Corinne; Brooker, Lance; Goebel, Catrin; Morrow, Ryan; Chakrabarty, Rima; Speers, Naomi; Molina, Adeline; Ericsson, Magnus; Collomp, Katia (Frontiers in Sports and Active Living, 2023)
Like any athlete, female athletes may be tempted to use prohibited substances during competition or training to enhance their performance. Anti-doping tests performed on female athletes in summer Olympic sports from two geographical areas: Australia/ New Zealand, and France were compared. First, the distribution of sample collections across different sports disciplines, as well as the distribution of substances was investigated. Then the distribution of collections and substances detected in the five sports categories (Strength/Speed, Endurance, Mixed, Motor Skills with High Energy Expenditure, and Motor Skills with Low Energy Expenditure) were studied with consideration of therapeutic use exemptions obtained by the athlete. Australia/New Zealand and France were similar in their overall number of anti-doping collections performed. Likewise, both regions had the same sports disciplines (athletics, aquatics, cycling) and sport categories (Mixed and Endurance) as having the highest number of sample collections. The Motor Skills with High Energy Expenditure, and Motor Skills with Low Energy Expenditure categories had the lowest number of sample collections. However, the number of substances detected was significantly different (p < 0.05) with a greater number of substances found in the French data. There were a few substances in common between the two geographical areas, namely prednisone/prednisolone, carboxy-THC, terbutaline, vilanterol and methylphenidate, but most were different. In-competition tests were the category where most of the AAFs were found.